2019
DOI: 10.3390/polym11091511
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ag Doped Keratin/PA6 Nanofiber Membrane with Enhanced Air Filtration and Antimicrobial Properties

Abstract: Coarse wool is a kind of goat wool that is difficult to further process in the textile industry due to its large diameter, dispersion, better strength, and less bending. Therefore, coarse wool is often discarded as waste or made into low-cost products. In this work, keratin was extracted from coarse wool by a high-efficiency method, and then, an Ag-doped keratin/PA6 composite nanofiber membrane with enhanced filtration and antibacterial performance was prepared using HCOOH as solvent and reductant. HAADF-STEM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Further investigation of a different fiber orientation could lead to interesting results, which would open up the possibility of developing high‐strength nanofibre keratin. Shen et al 109 reported the filtration efficiency of the silver nanoparticles doped with keratin/polyamide6 nanofibre membrane. Nanofibres have been developed with varying percentages of keratin (0%, 30%, 50%, and 70%).…”
Section: Biodegradable Natural Polymer Based Nanofibresmentioning
confidence: 99%
“…Further investigation of a different fiber orientation could lead to interesting results, which would open up the possibility of developing high‐strength nanofibre keratin. Shen et al 109 reported the filtration efficiency of the silver nanoparticles doped with keratin/polyamide6 nanofibre membrane. Nanofibres have been developed with varying percentages of keratin (0%, 30%, 50%, and 70%).…”
Section: Biodegradable Natural Polymer Based Nanofibresmentioning
confidence: 99%
“…The TRNG principle used by this system also mitigated the risk of ozone generation [ 73 ]. Biodegradable filters made of silk protein, called as silk nanofibrous air filters (SNAF), were also developed to separate PM 2.5 with a PFE of 97% and a QF of 0.3 at particle concentration of 444 μg/cm 3 [ 74 ]. Similar efficiencies were observed in silver (Ag)-doped keratin/nylon-6 nanofibrous composite membranes, where the average fiber sizes varied between 155 and 293 nm for various combination of silver doping and keratin concentration [ 75 ].…”
Section: Filtration Of Pms Using Ultrafine Fibersmentioning
confidence: 99%
“…Nanofibers as materials can be used as a platform in Raman spectroscopy [81], in immunoanalysis [82], for air filtration [83] and as a pseudo-enzyme [84]. As can be seen, the AgNPs, besides their important wound treatment activity, which is summarized in Table 3 below, can be used also for disinfection and catalytic purposes.…”
Section: Nanofibersmentioning
confidence: 99%